Increasing engagement through Towards a National Collection - Bailey, Rebecca (British Library, 2021)
At the centre of the £18.9m research development programme Towards a National Collection is the aim to increase engagement with the cultural heritage collections of the UK. Funded by the Arts and Humanities Research Council, the programme is working to link collections and encourage cross-searching of multiple collection types, to enable research and enhance public engagement. This presentation will outline the achievements and ambitions of the funded projects, and start to look ahead to a national collections research infrastructure.